EVOLUSI TEKTONIK BERDASARKAN ANALISIS DATA KEKAR DAERAH BINUANG DAN SEKITARNYA, KECAMATAN BINUANG, KABUPATEN TAPIN, PROVINSI KALIMANTAN SELATAN - Yusuf, Andi Supian; -, Ismawan; Helmi, Faisal (Fakultas Teknik Geologi Universitas Padjadjaran, 2014)
Research area administratively located in Binuang district, Tapin Regencies, South Kalimantan Province. Geographically located in coordinate 115° 3' 40,359